A histopathological significance in the detection of adrenocortical carcinoma, an unprecedented condition - Vidhya, G (Indian Journal of Case Reports, 2026)
Adrenocortical carcinoma (ACC) often remains undiagnosed due to its subtle and variable symptoms. This highlights the need for radiological, immunohistochemistry, and histopathological studies to identify the disease and grade the condition. This case report emphasizes the role of immunohistochemistry and histopathological findings in establishing an accurate diagnosis and guiding management. A 64-year-old woman with high blood pressure on medications (160/100 mmHg), on-and-off abdominal pain radiating to the back, gurgling and rumbling abdominal sounds, and an irreducible umbilical hernia underwent radiological studies, which revealed hypodense lesions noted in the adrenal gland and right suprarenal region. Subsequently, computed tomography contrast studies confirmed a right renal complex cyst classified as Bosniak IV. The patient underwent total nephrectomy, resulting in a significant reduction in blood pressure on medication (110/70 mmHg). A follow-up over 3 months showed sustained improvements. Histopathological examination and immunohistochemistry grading confirmed that the primary ACC metastasized into the upper pole of the right kidney, offering a novel and comprehensive therapeutic strategy.